THE EFFECT OF BASIC LIFE SUPPORT FIRST AID TRAINING ON CLEANING SERVICES AT MUHAMMADIYAH UNIVERSITY GORONTALO - Pipin Yunus; Haslinda Damansyah; Farel Novriyanto W. Kahar (LPPM Universitas An Nuur, 2026)
Background: Basic Life Support is the initial treatment for patients experiencing cardiac arrest, respiratory arrest or airway obstruction. Skills in this initial aid action aim at emergency oxygenation to maintain cardiopulmonary function through artificial ventilation and circulation. The aim of this research was to determine the effect of basic life support first aid training on cleaning service skills at Muhammadiyah University Gorontalo. Methods: This research method is quantitative and uses a quasi-experimental design with a one group pre test – post test design. Samples were taken using a total sampling technique with a total of 22 respondents. Data collection uses assessment observation sheets and basic life support SOPs. Data analysis used the paired t-test. Results: The research results showed that there were differences and improvements before and after treatment with a p-value of 0.000 (p<0.05). Conclusion: So it can be concluded that there is an influence of basic life support first aid training on 3 respondents with skilled skills and 19 respondents with quite skilled skills on cleaning services at Muhammadiyah University Gorontalo.